تأثير استخدام بعض الأوساط العضوية في إنتاج شتول نباتي الزينيا (Zinnia elegans)والمنثور(Matthiola incana) - نصور, مازن (Latakia University Journal -Biological Sciences Series, 2018)
نفذ هذا البحث في المشتل التابع لكلية الزراعة جامعة تشرين خلال عامي 2016 - 2017 بهدف دراسة إمكانية إنتاج شتول نباتي الزينيا و المنثور باستخدام أوساط عضوية مختلفة قليلة التكاليف مقارنةً بوسط التورب الأكثر استخداماً. تم استخدام سبعة أوساط (التورب، مخلفات كمبوست الفطر و كمبوست مخلفات المزرعة بالإضافة إلى التوافقات فيما بينها و بنسب متساوية). أظهرت النتائج وجود بعض الاختلافات في المواصفات الفيزيائية و الكيميائية للأوساط المختبرة، و التي انعكست على كل من مؤشرات الإنبات(نسبة الإنبات، سرعة الإنبات، تجانس الإنبات) بالإضافة إلى توعية الشتول المنتجة (طول الشتول و قطر ساقها، الوزن الرطب و الجاف و نسبة المادة الجافة للمجموعين الخضري و الجذري). حققت الأوساط الثلاث }التورب (T1)، مخلفات كمبوست الفطر مع التورب (T6)، مخلفات كمبوست الفطر مع كمبوست مخلفات المزرعة{ (T7) أفضل النتائج من حيث نسبة الإنبات و نوعية الشتول المنتجة. انعكست التأثيرات الإيجابية للأوساط العضوية المستخدمة في نوعية الشتول على الكفاءة الاقتصادية، حيث حقق الوسطان T3 وT7 أقل تكلفة و أعلى معامل ربحية مقارنةً بالأوساط الأخرى. The present investigation was carried out at the nursery of Agricultural faculty- Tishreen University, during 2016-2017, to evaluate the best organic culture medium for the seedling production of Zinnia (Zinnia elegans) and Stock (Matthiolaincana) with the lowest costs. Seven different mediums were experimented (Turf, waste mushroom compost, farm waste compost and their combinations). The results showed some differences in chemical and physical characters of experimented mediums. This differences had an impact on germination parameters (seed germination percentage, speed of germination, daily germination) and seedling quality (seedling length, collar diameter, fresh and dray weight, percentage of dray matter). The results indicated the mediums consisting of turf (T1), waste mushroom compost with turf (T6) and waste mushroom compost with farm waste compost (T7) gave the best germination rate and the highest quality of seedling. Data showed as well that T3 and T7 treatments realized the lowest costs and higher economic profit than other treatments.